The Association between Retinopathy and Arthritis: Findings from a US National Survey 2005-2008. (1st December 2020) - Zhu, Zhuoting; Liao, Huan; Scheetz, Jane; Zhang, Jian; He, Jingyi; Wang, Wei
ABSTRACT: Objective To explore the association between retinopathy and arthritis in a representative sample in the United States. Methods National Health and Nutrition Examination Survey (NHANES) is a series of biannual surveys in a nationally representative non-institutionalized population of the United States. Two waves of NHANES (2005–2008) were merged in the current analysis. Arthritis status and types of arthritis were obtained from questionnaires. Non-mydriatic fundus photographs were collected among participants aged 40 years and older and retinopathy status was assessed using the Airlie House classification scheme. The association between arthritis and retinopathy was evaluated using logistic regression models. Results From 6, 797 eligible participants, 4, 901 had information in terms of arthritis status and gradable fundus photographs of at least 1 eye. Retinopathy was less prevalent in patients with osteoarthritis compared with those without osteoarthritis (11.9% vs 17.5%, P < .05). Participants who had osteoarthritis had 43% reduced relative risk of retinopathy compared to those without, after adjusting for covariates (Odds Ratio [OR] = 0.57, 95% Confidence Interval [CI]: 0.33–0.98). This significant association persisted among diabetic participants (OR = 0.43, 95% CI: 0.19–1.00). However, no significant associations between any arthritis, rheumatoid arthritis, other types of arthritis and retinopathy were noted. Conclusions Patients with osteoarthritis were less likely to have retinopathy when compared with those without. Further studies investigating the possible protective effects of arthritis physiology and/or arthritis treatment in retinopathy are needed.